The Role of Dendritic Cells in Graft-Versus-Tumor Effect - Reddy, Pavan; Toubai, Tomomi; Mathewson, Nathan (Frontiers in Immunology, 2014)
Dendritic cells (DCs) are the most potent antigen presenting cells. DCs play a pivotal role in determining the character and magnitude of immune responses to tumors. Host and donor hematopoietic-derived DCs play a critical role in the development of graft-versus-host disease (GVHD) following allogeneic hematopoietic cell transplantation. GVHD is tightly linked with the graft-versus-tumor (GVT) effect. Although both host and donor DCs are important regulators of GVHD, the role of DCs in GVT is poorly understood. GVT is caused by donor T cells that attack recipient tumor cells. The donor T cells recognize alloantigens, and tumor specific antigens (TSAs) are mediating GVHD. The process of presentation of these antigens, especially TSAs remains unknown. Recent data suggested that DC may be essential role for inducing GVT. The mechanisms that DCs possess may include direct presentation, cross-presentation, cross-dressing. The role they play in GVT will be reviewed.